Diameter Increment in Artocarpus hirsuta, Dalbergia latifolia and Grewfa tilaefolia in the Mixed Deciduous Forests of Wynaad (kerala) - Rai, S. N.; Sarma, C. R. (Indian Forester, 1993)
The annual diameter increment in Artocarpus hirsuta, Dalbergia latifolia and Grewia tilaefolia were studied in the mixed deciduous forests of Wynaad, over a period of 16 years. The increments were found to be 0.48 cm, 0.34 cm and 0.33 cm respectively over the range of diameter studied. Artocarpus hirsuta take 137 years, Dalbergia lotifdia 148 years and Grewia Ioaefolia 168 years to reach 60 cm of D.B.H. in these forests.